Synthesis, structural, electrochemical and corrosion inhibition properties of two new ferrocene Schiff bases derived from hydrazides - Gupta S.R.; Mourya P.; Singh M.M.; Singh V.P. (My University, 2025)
Two new Schiff bases, ferrocene carboxaldehyde propanoylhydrazone (fcph) and ferrocene carboxaldehyde furoylhydrazone (fcfh) have been synthesized and characterized by elemental analyses, electronic, IR and NMR spectral studies. Molecular structures of fcph and fcfh are determined by single crystal X-ray diffraction technique. The Schiff bases fcph and fcfh display E-configuration about the >CN- bond. The structures of both the compounds are stabilized by inter-molecular H-bonding. The electrochemical study of these compounds exhibits quasi-reversible one electron redox behaviour. The corrosion inhibition study of the Schiff bases have been performed by using weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements. The compounds fcph and fcfh show an appreciable corrosion inhibition property against corrosion of mild steel in 0.5 M H2SO4 solution at 298 K. It has been observed that fcfh shows greater corrosion inhibition efficiency than fcph. As the concentration of the Schiff bases increases, corrosion inhibition property of the compounds increases. © 2014 Elsevier B.V. All rights reserved.